2020
DOI: 10.3390/antiox9090868
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic Cardiovascular Exercise Training Alters Redox Status, Reduces Inflammation and Improves Physical Performance in Patients with Chronic Kidney Disease

Abstract: Redox status (RS) perturbations and inflammation are fundamental features of chronic kidney disease (CKD) that are substantially exacerbated in end-stage renal disease (ESRD). This study aimed at investigating the efficacy of a 6-month intradialytic exercise training program on RS, inflammation and physical performance in patients with ESRD. Twenty hemodialysis (HD) patients (17 males, three females) were randomly assigned to either an intradialytic training (bedside cycling) group (TR; n = 10) or a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…Of the non-pharmacological interventions, regular physical activity has a positive effect on fatigue 139 . Intradialytic cardiovascular exercise training reduced inflammation and improved physical performance in patients receiving HD 140 . A systematic review comprising 20 trials (677 participants) 141 reported that aerobic and combined exercise was useful for improving QOL in patients treated with HD.…”
Section: Global Patient-reported Outcomesmentioning
confidence: 94%
“…Of the non-pharmacological interventions, regular physical activity has a positive effect on fatigue 139 . Intradialytic cardiovascular exercise training reduced inflammation and improved physical performance in patients receiving HD 140 . A systematic review comprising 20 trials (677 participants) 141 reported that aerobic and combined exercise was useful for improving QOL in patients treated with HD.…”
Section: Global Patient-reported Outcomesmentioning
confidence: 94%
“…The 24 studies included were conducted in Iran [ 19 ], Brazil [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], Poland [ 30 ], the United Kingdom [ 31 , 32 , 33 , 34 , 35 , 36 ], Taiwan [ 37 ], China [ 38 ], Indonesia [ 39 ], Spain [ 40 , 41 ] and Greece [ 42 ], and published from 2010 to 2022.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are presented in Table 1 . The 24 studies were clinical trials, of which thirteen were randomized controlled trials [ 19 , 25 , 26 , 27 , 28 , 29 , 35 , 36 , 37 , 38 , 39 , 41 , 42 ], four were uncontrolled trials [ 20 , 21 , 30 , 40 ], one was a non-randomized clinical trial [ 23 ], one was a non-randomized controlled trial [ 32 ], four were randomized crossover trials [ 22 , 24 , 31 , 33 ], and one was a non-randomized crossover trial [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations